Efficacy and safety of Melaleuca alternifolia (tea tree) oil for human health—A systematic review of randomized controlled trials - Kairey, Lana; Agnew, Tamara; Bowles, Esther Joy; Barkla, Bronwyn J.; Wardle, Jon; Lauche, Romy (Frontiers in Pharmacology, 2023)
Leaves of the Australian tea tree plant Melaleuca alternifolia were used traditionally by indigenous Australians for treating wounds, burns, and insect bites. Tea tree oil, the essential oil steam-distilled from Melaleuca alternifolia, is well-known for its medicinal properties, the evidence for most applications however is limited. This review aimed to critically appraise evidence from clinical trials examining the therapeutic efficacy and safety of tea tree oil on outcomes. Randomized controlled trials with participants of any age, gender, or health status, comparing tea tree oil to any control were included, without limit on publication date. Electronic databases were searched on 12 August 2022 with additional records sourced from article reference sections, reviews, and industry white papers. Risk of bias was assessed by two authors independently using the Cochrane risk-of-bias 1.0 tool. Results were summarized and synthesized thematically. Forty-six articles were eligible from the following medical fields (Dentistry n=18, Dermatology n=9, Infectious disease n=9, Ophthalmology n=6, Podiatry n=3; and Other n=1). Results indicate that oral mouthwashes with 0.2-0.5% tea tree oil may limit accumulation of dental plaque. Gels containing 5% tea tree oil applied directly to the periodontium may aid treatment of periodontitis as an adjunctive therapy to scaling and root planing. More evidence is needed to confirm the benefits of tea tree oil for reducing acne lesions and severity. Local anti-inflammatory effects on skin, if any, also require further elucidation. Topical tea tree oil regimens show similar efficacy to standard treatments for decolonizing the body from methicillin-resistant Staphylococcus aureus, although intra-nasal use of tea tree oil may cause irritation to mucous membranes. Tea tree oil with added iodine may provide an effective treatment for molluscum contagiosum lesions in young children. More evidence on efficacy of tea tree oil-based eyelid wipes for Demodex mite control are needed. Side effects were reported in 60% of included studies and were minor, except where tea tree oil was applied topically in concentrations ≥25%. Overall, the quality of research was poor to modest and higher quality trials with larger samples and better reporting are required to substantiate potential therapeutic applications of tea tree oil.